2021
DOI: 10.1016/j.breast.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Survival in breast cancer patients with a delayed DIEP flap breast reconstruction after adjustment for socioeconomic status and comorbidity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Women with breast cancer undergoing breast reconstruction are commonly younger and healthier, and have a higher socioeconomic status than their counterparts not receiving reconstruction 23 , 24 . Women who undergo breast reconstruction tend to have better survival than those with comparable disease and treatment characteristics, suggesting a selection bias present at the time of surgical planning 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…Women with breast cancer undergoing breast reconstruction are commonly younger and healthier, and have a higher socioeconomic status than their counterparts not receiving reconstruction 23 , 24 . Women who undergo breast reconstruction tend to have better survival than those with comparable disease and treatment characteristics, suggesting a selection bias present at the time of surgical planning 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of subgroup analysis showed that OS was better for those receiving ABR who lived in urban areas. Some studies have shown that patients receiving ABR have higher education compared to mastectomy patients (43), and patients with commercial insurance and higher levels of education were more likely to undergo post-mastectomy reconstruction (44). These social factors can lead to a positive impact in OS, but it is difficult to evaluated this impact.…”
mentioning
confidence: 99%